Pengaruh Modal, Jam Kerja dan Pemanfaatan Marketplace terhadap Produktivitas dan Pendapatan Rumah Makan di Kecamatan Kuta - Ni Kadek Ayu Cahyaningsih; Made Heny Urmila Dewi (Jurnal Syntax Admiration, 2023)
The food and beverage sector, such as SME restaurants, is one of the most influential sectors in the development of the tourism sector in Badung Regency. Kuta District is the area with the largest number of SME restaurants in Badung Regency. During the Covid - 19 pandemic, the food and beverage industry sector experienced a decline as indicated by the decreasing number of restaurants in Kuta District. During the Covid - 19 pandemic and with the enactment of PPKM regulations in the community, many restaurants in Kuta District switched to trying to utilize marketplace media such as Go - Food, GrabFood, ShopeeFood and so on in maintaining the level of productivity and restaurant income during the Covid - 19 pandemic. The purpose of this study was to determine the effect of capital, working hours and marketplace utilization on the productivity and income of restaurants in Kuta District. The number of samples in this study were 130 and for the method of determining the sample using purposive sampling technique. The analysis technique used in this research is descriptive analysis and path analysis. Based on the results of the study, the variables of capital, working hours and marketplace utilization have a positive and significant effect on the productivity of restaurants in Kuta District. The results of this study also show that the variables of capital and working hours have a positive and significant effect while, for the marketplace utilization variable shows the results have a negative and insignificant effect on the income of restaurants in Kuta District. The results of this study also show that the productivity variable is an intervening variable that mediates the effect of capital, working hours and marketplace utilization on restaurant income in Kuta District.